PENEGAKAN HAK KORBAN KEKERASAN DALAM RUMAH TANGGA MENURUT UNDANG-UNDANG NOMOR 23 TAHUN 2004 : Peneggakan Hukum, Tindak Pidana, Kekerasan Dalam Rumah Tangga. - Siti Rahmah; Darmiwati (JURNAL HUKUM DAS SOLLEN, 2022)
ABSTRACT The crime of violence against women in the household is an act of violence or threats, pressure and coercion that can injure or physically interfere with the life of women in the household is wrong treatment, the crime of violence against women includes the level of severe violence because the form of violence committed is fatal. cause physical damage as a result of punching, beating, burning that can damage the body. normative legal research, namely library law research. Based on the division of normative legal research, this research includes research that focuses on research on the Statute Approach and Conceptual Approach. The Legislative Approach (Statute Approach) examines various legal rules that are the focus and central theme of a study. Conceptual Approach are elements that represent phenomena in a field of study that refer to universal things that are abstracted from particular things. If the domestic violence experienced by the victim is not revealed or not resolved, then the protection of the victim of this crime cannot be provided adequately because the violence experienced by the victim is not reported to the police to handle the case and during this time there are many thoughts that have been brought to justice. the perpetrator of the crime and then the perpetrator undergoes a sentence, then legal protection to the victim is considered to have been fully provided. In the settlement of criminal cases, the law often puts too much emphasis on the rights of the suspect or defendant, while the rights of the victim are ignored. Keywords: Law Enforcement, Crime, Domestic Violence